TRENDS, GROWTH AND INSTABILITY IN COTTON CROP PRODUCTION IN KURNOOL DISTRICT, ANDHRA PRADESH, INDIA - K, Dr. Visweswara Reddy; E, Dr. Lokanadha Reddy (Economics and Statistics Research Journal (ESRJ), 2023)
Optimal site for locating borehole has been delineated on the basis of empirically derived aquifer hydraulic parameters. To that end, seventeen VES data were quantitatively interpreted via partial curve matching technique and the starting models refined by means of 1D Forward modelling with iteration to obtain geoelectric characteristics. The results indicted presence of varying geo-electric earth-layer models, ranging from 3- to 5- earth-layer models. Curve type analysis revealed that Htype and HA-type curves are predominant in the study area. The conceptual aquifer model showed a preponderance of Weathered/fractured aquifer systems archetypal to basement complex environments. The aquifer unit resistivity ranges from 5.6 – 751.6 ohm-m with low values symptomatic of clay materials. The aquifer layer thickness vary from 1.6 m to 48.3 m with an average of 13.6 m. Hydraulic conductivity values for the study area ranges from 0.005 – 11.99 m/day with most of the study area having low hydraulic conductivities. Transmissivity within the study area ranged from 0.03 - 141.6 m2/day, corresponding to log transformed transmissivity ranging from 2.50 m2/day to 6.20 m2/day. The log transmissivity result was used to classify the study area into five zones based on Krasny Classification Scheme; Imperceptible (< 3 m2/day), Very Low (3 m2/day), Low (4 m2/day), Intermediate (5 m2/day) and High (6 m2/day) groundwater potential zones. The findings showed that 80% of the study area falls within Very Low and Low transmissivity classification (3 – 4 m2/day), correlating with zones of Low hydraulic conductivity and boreholes sited can only sustain small withdrawals for sequestered consumption. Optimal borehole site is limited to a small area (3.5 m2) of high transmissivity where abstraction for regional purposes is supported